Emerging local delivery strategies to enhance bone regeneration. (20th November 2020) - Elangovan, Satheesh; Gajendrareddy, Praveen; Ravindran, Sriram; Salem, Aliasger K
Abstract: In orthopedics and dentistry there is an increasing need for novel biomaterials and clinical strategies to achieve predictable bone regeneration. These novel molecular strategies have the potential to eliminate the limitations of currently available approaches. Specifically, they have the potential to reduce or eliminate the need to harvest autogenous bone, and the overall complexity of the clinical procedures. In this review, emerging tissue engineering strategies that have been, or are currently being, developed based on the current understanding of bone biology, development and wound healing will be discussed. In particular, protein/peptide based approaches, DNA/RNA therapeutics, cell therapy, and the use of exosomes will be briefly covered. The review ends with a summary of the current status of these approaches, their clinical translational potentials and their challenges.